Ultraviolet reflectance and pattern properties in leopard geckos (Eublepharis macularius) - Abramjan, Andran; Baranová, Veronika; Frýdlová, Petra; Landová, Eva; Frynta, Daniel (Behavioural processes, 2020)
Complex visual signaling through various combinations of colors and patterns has been well documented in a number of diurnal reptiles. However, there are many nocturnal species with highly sensitive vision, being able to discriminate colors in night conditions, as was shown in geckos. Because of their sensitivity to chromatic signals, including UV (ultraviolet), they may have potential hidden features in their coloration, which may play role in intraspecific communication (e.g. mate choice) or interspecific signals (e.g. antipredatory function). We explored this hypothesis in nocturnal Leopard geckos (Eublepharis macularius), a species using visual signals in both antipredation defense and courtship, having ontogenetic color change accompanied by a shift in behavior. We used UV photography and visual modeling in order to compare various aspects of their coloration (luminance, contrast, color proportions) between sexes, age groups and populations. We found that Leopard geckos have considerable UV reflectance in white patches on their tails (and on the head in juveniles). Though, no prominent differences were detected in their coloration between various groups. We hypothesize that the limitation of UV reflectance to the head and tail, which are both actively displayed during defense, especially in juveniles, might potentially boost the effect of antipredation signaling.
Keywords: Sex Factors; Pattern Recognition, Visual; Color Vision; ještěři; Night Vision; Female; věkové faktory; zvířata; Photic Stimulation; ultrafialové záření; světelná stimulace; noční vidění; sexuální faktory; rozpoznávání obrazu; ženské pohlaví; Male; vidění barevné; Lizards; Ultraviolet Rays; Age Factors; Animals; mužské pohlaví